PENGELUARAN RUMAH TANGGA PETANI KARET DI DESA PULAU JAMBU KECAMATAN KUOK KABUPATEN KAMPAR - Arif Suganda; Shorea Khaswarina; Eliza ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purposes of this research are 1) To determine the pattern of food and non food expenditure of households 2) To determine the ability of farmers to meet the basic needs based on the criteria of BPS. This research was conducted at Pulau Jambu village, Kuok district, Kampar regency in April to July 2014. The method of sampling in this study was randomly and took 60 farmers as respondent. Analysis of the data for the study was by counting household expenditures and based on 14 indicators of basic needs in 2008 according to the BPS. The household expenditure’s average of rubber farmers in Pulau Jambu village is Rp. 3,150,800 per month divided into food and non-food expenditures. The total average of household expenditure across the sample rubber farmers reached Rp. 189,048,000 per month. The fulfillment of basic needs of households that have been analyzed by the 14 criterias for basic needs according to the BPS that indicates the rubber farmers in the Jambu village is not included to the category of near-poor. Keywords: Expenditure, Households, Rubber Farmers.